Action of antimicrobial peptides and their prodrugs on model and biological membranes. (24th May 2018) - Forde, Éanna; Shafiy, Ghady; Fitzgerald‐Hughes, Deirdre; Strömstedt, Adam A.; Devocelle, Marc
Abstract : Antimicrobial peptides (AMPs) are promising broad‐spectrum antibiotic candidates in the wake of multi‐drug resistant pathogens. Their clinical use still requires a solution based on lead optimisation and/or formulation to overcome certain limitations, such as unwanted cytotoxicity. A prodrug approach could overcome this safety barrier and can be achieved through reversible reduction or neutralisation of the AMPs' net cationic charge. By prodrug activation through pathogen associated enzymes, this approach could increase the therapeutic index of membrane active peptides. P18, a cecropin/magainin hybrid, and WMR, a myxinidin analogue from hagfish, were used as templates for the design strategy. The membrane permeabilizing activities of these AMPs and their prodrugs are reported here for liposomes of either Escherichia coli polar lipid extract or a human model lipid system of phosphatidylcholine and cholesterol. These results are compared with their antibacterial and haemolytic activities. Overall, correlation between liposome permeabilization and the corresponding bioactivity is observed and indicate that the broad‐spectrum antibacterial effect exerted by these peptides is associated with membrane disruption. Furthermore, the prodrug modification had a general negative influence on membrane disruption and bioactivity, notably as much on bacterial as on human membranes. This prodrug strategy is particularly successful when complete neutralisation of the AMP's net charge occurs. Thus, on‐target selectivity between bacterial and human membranes can be improved, which may be used to prevent the unnecessary exposure of host cells and commensal bacteria to active AMPs. Abstract : The membrane permeabilizing activities of 2 AMPs and their prodrugs are compared with their antibacterial and haemolytic activities. Overall, correlation between liposome permeabilization and the corresponding bioactivity indicate that the broad‐spectrum antibacterial effect exerted by these peptides, as well as the (desired) general negative effect exerted by the promoiety, is associated with membrane disruption.